Report on Evaluation Study of Centrally Sponsored Package Programme for Cotton - Planning Commission (Planning Commission, 1978)
Realising that there were severe limits to a continuing extension of the area under cotton, the Centrally Sponsored Scheme for Maximised production of Cotton for increasing the yield per hectare was initiated in 1936-67. The scheme was sought to be implemented through a variety of measures, such as production of improved varieties of nucleus and foundation seeds, mass plant protection campaigns, foliar application of urea, demonstrations, grading of Kapas, etc. Under this programme the Central Government gave subsidy to the States on the major inputs.
Programme Evaluation Organisation Planning Commission Government of India